The Effect of Motivation, Discipline and Job Satisfaction on Employee Performance in Printing Division PT. Yasunli Abadi Utama - Posman WH Hasibuan; Swasta Bangun (Journal of Research in Business, Economics, and Education, 2021)
This research was conducted to determine the effect of motivation, discipline and job satisfaction on employee performance. This research is a quantitative research using multiple regression analysis to find the value of the regression coefficient of each independent variable in this study, namely motivation, discipline and job satisfaction while the dependent variable is employee performance. The population in this study were employees of the Printing Division of PT. Yasunli Abadi Utama. Determination of the sample of this study using probability sampling technique with a simple random method (simple random sampling). The sample in this study were 67 people. While the types of data used are library research and field research with data collection techniques using questionnaires, observation. The technique used to analyze the data are: multiple linear regression analysis, using the t hypothesis test and the F hypothesis test and analysis of the coefficient of determination. From the research results, the regression coefficient value of the motivation variable is 0.231 where the value of t count = 2.501 > t table = 1.9983 with a significance of 0.001 which indicates that the motivation variable significantly affects employee performance, as well as the regression coefficient value of discipline of 0.420 where the value of t count = 4.660 > t table 1.9983 with a significance of 0.000 < 0.05 which indicates discipline affects employee performance and the regression coefficient value of the job satisfaction variable is 0.388 where the value of t count = 4.155 > t table = 1.9983 with a significance 0.000 <0.05 which indicates job satisfaction significantly affects performance. Then from the simultaneous test where the calculated F value = 103.571 > F arithmetic = 4.13 with a significance of 0.000 <0.05 which means that simultaneously the motivation, discipline and job satisfaction variables can significantly affect the performance of employees in the printing division of PT. Yasunli Abadi Utama. Furthermore, from the analysis of the coefficient of determination (R2) simultaneously of 0.831 which shows that 83.1% of the variation in employee performance can be explained by the variables of motivation, discipline and job satisfaction of employees in the printing division of PT. Yasunli Abadi Utama. The conclusion from the results of this study is that the increase in employee performance cannot be separated from motivation (safety and security needs, salary and wage needs, self-esteem needs, and love and social needs), Discipline (always present on time, always using working hours effectively and efficiently , complete work on time, have high morale and work as a team), Satisfaction (have work skills in their field of work, get good work results according to expertise, have supporting equipment and equipment, get more appreciation if you do a good job, get moral support from colleagues and superiors in case of problems) . With high work motivation, work discipline and job satisfaction, it will be easier to improve employee performance.